Oldest colobine calcaneus from East Asia (Zhaotong, Yunnan, China). Issue 147 (October 2020) - Ji, Xueping; Youlatos, Dionisios; Jablonski, Nina G.; Pan, Ruliang; Zhang, Chunxia; Li, Pei; Tang, Min; Yu, Tengsong; Li, Wenqi; Deng, Chenglong; Li, Song
Abstract: Apart from a juvenile hominoid, the locality of Shuitangba (southwestern China, 6.5–6.0 Ma) has yielded a mandible and proximal femur attributed to the colobine genus Mesopithecus. A complete colobine calcaneus also accompanies this material, but its association with the other Mesopithecus material remains to be confirmed. These fossil elements are very important as they represent the oldest known colobines from East Asia, extend the dispersal of Mesopithecus to southwestern China, and underscore its close affinities and potential ancestry to the odd-nosed colobines. The present article focuses on the functional morphology of this complete calcaneus to reconstruct the positional habits, infer the paleocology, and understand the dispersal patterns of this fossil colobine. The studied characters corroborate the attribution of this element to colobines and support potential affinities with the Mesopithecus remains of the same locality. Functionally, characters such as the long and narrow tuber calcanei, the short proximal calcaneal region, and the relatively extended and long and narrow proximal calcaneoastragalar facet appear to enable habitual pedal flexion with conjunct inversion that accommodate the foot on diversely oriented and differently sized arboreal substrates. On the other hand, the relatively short distal calcaneal region is functionally related to (mainly terrestrial) quadrupedal activities, wherein thrust and rapid flexion are required. This combination of characters suggests that the Shuitangba colobine could move at ease on arboreal substrates and was also able to occasionally use terrestrial substrates. The potential affinities of this calcaneus to Mesopithecus and its positional profile most likely imply an eastward migration via forested corridors. In Shuitangba, this fossil colobine could trophically and positionally exploit a wide range of habitats successfully coexisting with resident hominoids.